The Preservation of Adobe Buildings - Diana Plian; Dan Babor (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2010)
Whether built in the 17th or in the 20th centuries, adobe buildings share common problems of maintenance and deterioration. These types of buildings represent today in Romania a traditional house for country people. It also makes recommendations for preserving adobe buildings. By its composition, adobe construction is inclined to deteriorate; however, the buildings can be made durable and renewable when properly maintained.